Chemical and Geochemical Characteristics of the major Minerals in the ore Deposit Mitrašinci (Eastern Macedonia) (Geologica Macedonica, 2013)
The chemical examinations of individual grains as well as monomineral fractions of magnets are made towards possible concentrations of major and element impurity and for that purpose the magnets from the Mitrašinci vicinity are embraced. The results of these examinations made on partial individuas as well as separated monomineral fractions of the magnetite, give basic data for the concentration of the major and elemental impurity in exanimated magnets in the Mitrašinci vicinity. Together with the examinations that are made on the magnets of the Mitrašinci vicinity, it is posited that some element impurity are concentrated constant in them, during some elements are concentrated occasionally. From the element impurity in the crystal structure of the magnets from the Mitrašinci vicinity there are: Cr, Ti, V, Mn, Ni, Co, Zn, Mg and Al. Si and Ca are also incorporated. In these paper the results from the latest examinations of partial individual and monomineral testing of the magnetite will be shown, and they are referring on the element impurity presence of the above mentioned minerals.